A comparative study of diagnostic accuracy in 3026 pleural biopsies and matched pleural effusion cytology with clinical correlation. (18th July 2022) - Poon, Ivan K.; Chan, Ronald C. K.; Choi, Joseph S. H.; Ng, Joanna K. M.; Tang, Katsie T.; Wong, Yolanda Y. H.; Chan, Ka Pang; Yip, Wing Ho; Tse, Gary M.; Li, Joshua J. X.
Abstract: Background: Pleural effusion can be caused by a wide range of benign and malignant conditions. Pleural biopsy and effusion cytology represent two key methods of pathological diagnosis. To compare the performance these two methods, a large cohort of matched pleural biopsy and effusion cytology with clinical follow‐up was reviewed. Methods: Pleural biopsies and effusion cytology specimens over a period of 18 years were retrieved. Cytology specimens collected within 7 days of pleural biopsy were matched. Reports were reviewed, and the cause for pleural effusion was determined by hospital disease coding and clinical data. Results: Totally, 3026 cases were included. The leading cause of benign effusion was tuberculosis ( n = 650). Malignant pleural effusion (MPE) was more common in older females ( p < 0.001) and mostly due to lung cancer ( n = 959), breast cancer ( n = 64), and mesothelioma ( n = 48). The inadequate/insufficient (B1/C1) rate of biopsy was higher than cytology (15.6% vs. 0.3%) but the rates for other diagnostic categories were similar. Biopsy and cytology showed a correlation coefficient of 0.315, improving to 0.449 when inadequate/insufficient (B1/C1) cases were excluded. The ROM for benign cytology (C2) was lower than biopsy (B2) ( p < 0.001). Compared with biopsy, the diagnostic accuracy was higher in cytology overall and for metastatic carcinomas ( p < 0.001) but lower for hematolymphoid malignancies ( p = 0.014) and mesotheliomas ( p = 0.002). Conclusions: These results suggest that effusion cytology may be better for confirming benignity and diagnosing carcinomatous MPE. In these cases, pleural biopsy may be withheld to reduce procedural risks. However, for suspected hematolymphoid malignancies and mesothelioma, biopsy should be considered. Abstract : Effusion cytology is superior to pleural biopsy in excluding malignant pleural effusion and diagnosis of metastatic carcinomas.